Processes of communication and dissemination of science: the challenges of science policy guidelines in Colombia - Niño-Sandoval, Yaddy; Alvarez-Risco, Aldo; Simbaqueba-Uribe, John; Del-Aguila-Arcentales, Shyla; Villalobos-Alvarez, Diego; Yañez, Jaime A. (Frontiers in Education, 2023)
The present work aims to recognize the characteristics of the most recent public policy, generated between 2020 and 2021, on the communication of science, dissemination and Social Appropriation of Knowledge in Colombia, determine what are the incentives that are offered by politics to promote them, and the importance that is given from there to the use of digital scenarios. The above is done from a comparative analysis of Colombia's guidelines of public science policies from a bibliographical review. With this analysis, it is concluded that the policies resulting from 22 years of reflection in Colombia aim to strengthen the Social Appropriation of Knowledge from the communication of science, understood in specific relation to dissemination, which is understood as activities that make knowledge accessible to scientific knowledge to a much wider audience. The digital scenarios are proposed as communicative spaces to spread knowledge to a community and strengthen the cinematic-society relationship.